Better together: Potential of co-culture microorganisms to enhance bioleaching of rare earth elements from monazite. (September 2018) - Fathollahzadeh, Homayoun; Hackett, Mark J.; Khaleque, Himel N.; Eksteen, Jacques J.; Kaksonen, Anna H.; Watkin, Elizabeth L.J.
Abstract: The aim of this study was to develop continuous bioleaching of monazite by combining heterotrophic and autotrophic acidophilic microorganisms. The results showed that a co-culture of autotrophic, acidophilic Acidithiobacillus ferrooxidans and heterotrophic Enterobacter aerogenes was more effective in bioleaching rare earth elements (REEs) from monazite than either species alone. This was likely due to a synergic interaction through the biogenic generation of both organic acids and sulfuric acid. In conclusion, the consortium of E . aerogenes and A . ferrooxidans solubilised REEs (Ce, La, Nd, Pr, and Y) up to a final concentration of 40 mg L −1 . Highlights: Combined neutrophilic and acidophilic bacteria in monazite bioleaching was studied. Co-culture of both species was more effective in bioleaching than either alone. Interaction of organic and sulfuric acid play major role in bioleaching of monazite. Organization of pho operon may be responsible for differences in monazite bioleaching.